Improving skills of farmers and development agents on integrated pest and disease management on food legumes in Ethiopia - Kassaw, Admasie; Abtie, Abate; Assaye, Gebremariam; Abathun, Tamir; Bitew, Beyene; Ali, Bereket; Alem, Cherinet; Kemal, Seid Ahmed (International Center for Agricultural Research in the Dry Areas, 2022)
IPDM knowledge and skills of farming communities, especially women and youth, improved through formal and informal training workshops in target countries.